2015
DOI: 10.1109/jsac.2015.2430520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Position-Related Information in Multipath Components for Indoor Positioning

Abstract: Location awareness is a key factor for a wealth of wireless indoor applications. Its provision requires the careful fusion of diverse information sources. For agents that use radio signals for localization, this information may either come from signal transmissions with respect to fixed anchors, from cooperative transmissions inbetween agents, or from radar-like monostatic transmissions. Using a-priori knowledge of a floor plan of the environment, specular multipath components can be exploited, based on a geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 33 publications
1
151
0
Order By: Relevance
“…We further notice that BLE4.0 beacon ’Be08’ has been placed by the left edge of the entrance door, close to the a corridor with a glass wall, Figure 3d. Our choice has been based on recent results reported in the literature claiming that knowing the geometry of the experimental environment space may be exploited to develop more accurate indoor localization mechanisms [12]. …”
Section: Ble40 Indoor Localization: Set-up Tools and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further notice that BLE4.0 beacon ’Be08’ has been placed by the left edge of the entrance door, close to the a corridor with a glass wall, Figure 3d. Our choice has been based on recent results reported in the literature claiming that knowing the geometry of the experimental environment space may be exploited to develop more accurate indoor localization mechanisms [12]. …”
Section: Ble40 Indoor Localization: Set-up Tools and Algorithmsmentioning
confidence: 99%
“…As mentioned in the introduction, recent studies have shown that the use of a priori floor plan information may enable the development of more accurate wireless indoor localization schemes [12]. …”
Section: Asymmetric Transmission Powermentioning
confidence: 99%
“…To properly weigh the position-related information of each range measurement [38], their SINR values are determined, which now define the power ratios between the useful deterministic MPCs and the DM interference plus noise at the corresponding delays. The SINRs are related to the range uncertainties of the MPCs that are associated with VAs [42], [43]. An online estimation of these range uncertainties also allows for an efficient selection of the VAs that provide reliable position-related information.…”
Section: A Single-antenna Terminalsmentioning
confidence: 99%
“…6 [2], [43]. It can be seen that an error below 10 cm is achievable over almost the whole scenario with only a single anchor.…”
Section: A Single-antenna Terminalsmentioning
confidence: 99%
“…FI and CRB analysis has been fundamental to the estimation discipline for decades and is clearly applicable to the present application which is relating the accuracy of an MWD location estimator to the set of RSS observables. However, while there are some publications that refer to the FI related to RSS observables [5,6], there are additional and fundamental insights that can be gleaned. The objective of this paper is primarily to provide a more unified approach for the analysis of the FI over a set of RSS observables in the MWD location estimation context and in that process illuminate insights that have, in the authors’ opinion, hitherto been obscured.…”
Section: Introductionmentioning
confidence: 99%